Significance of CD44 and CD24 as Cancer Stem Cell Markers: An Enduring Ambiguity - Appalaraju Jaggupilli; Eyad Elkord (Clinical and Developmental Immunology)
Cancer stem cell population is a subset of cells capable of dictating invasion, metastasis, heterogeneity, and therapeutic resistance in tumours. Eradication of this rare population is a new insight in cancer treatment. However, prospective identification, characterization, and isolation of these CSCs have been a major challenge. Many studies were performed on surface markers for potential identification and isolation of CSCs. Lack of universal expression of surface markers limits their usage and no best combination of markers has yet been confirmed to identify CSCs capable of initiating and metastasizing tumours. CD44, a hyaluronic acid receptor, is one of the most commonly studied surface markers, which is expressed by almost every tumour cell. CD24, a heat stable antigen, is another surface marker expressed in many tumour types. However, their expression and prognostic value in isolating CSCs are still an enduring ambiguity. In this critical review, we assess the role of CD44 and CD24 in tumour initiation, development, and metastasis. We mainly focus on analysing the significance of CD44 and CD24 as CSC surface markers in combination or with other putative markers in different types of cancer.